2004
DOI: 10.1071/ea03219
|View full text |Cite
|
Sign up to set email alerts
|

Effective trapping methods for assessing invertebrates in vineyards

Abstract: There is increasing interest in developing environmental management systems to ensure that agricultural industries are sustainable; invertebrate indicators provide one potential tool for monitoring sustainable production. As a first step in developing invertebrate indicators for viticulture, we compare the efficiency of 3 common trapping methods in assessing populations of relevant orders of invertebrates. Yellow sticky traps were more effective in trapping Hymenoptera, Thysanoptera, Hemiptera, Diptera, Aranea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Yellow was especially effective in capturing parasitic Hymenoptera (Thomson et al, 2004). Mondor (1995) reported that high numbers of hoverflies (Syrphidae) were caught by sticky red spheres in an apple orchard in Bremden, Manitoba, Canada.…”
mentioning
confidence: 99%
“…Yellow was especially effective in capturing parasitic Hymenoptera (Thomson et al, 2004). Mondor (1995) reported that high numbers of hoverflies (Syrphidae) were caught by sticky red spheres in an apple orchard in Bremden, Manitoba, Canada.…”
mentioning
confidence: 99%
“…For instance, in Californian and South African vineyards, the invasive Argentine ant, Linepithema humile (Mayr), can significantly enhance hemipteran pest densities (Addison & Samways 2000;Daane et al 2007). However, while ants form a major component of ground invertebrates in vineyards (Thomson et al 2004), little is known about their broader impact in Australian vineyards. While their relationship with honeydew-producing hemipterans is unclear (Chong et al 2010), ants may play important predatory roles in suppressing various life stages of light brown apple moth, Epiphyas postvittana Walker (Lepidoptera: Tortricidae) (MacLellan 1973;Frank et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this trap method may be less efficient when monitoring cabbages in small field plots. Nevertheless, those traps proved effective for capturing very small, non-target insects, e.g., parasitic wasps, thrips, and species within Orius, which are not as easily identified during a visual survey Thomson et al (2004). have also shown that yellow sticky traps are suitable for monitoring small insects, such as Hymenopteran, Thysanopteran, and Hemipteran species.We determined that the composition of non-target arthropod species in the field did not differ between Bt and non-Bt plants.…”
mentioning
confidence: 97%